PENGEMBANGAN APLIKASI “PERANTARA” BERBASIS ANDROID SEBAGAI MEDIA PEMBELAJARAN IPS PADA MATERI INDONESIAKU KAYA BUDAYA KELAS IV - Lestari, Liza Rahma; Nurdinah Hanifah; Kusman Rukmana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In social studies education, it is expected that future generations will understand cultural diversity with responsibility and concern for global issues, in line with their educational level and maturity. However, there is a gap between expectations and reality, particularly in the material "Indonesiaku Kaya Budaya," where students often struggle to recognize various ethnic groups and their provinces. The abstract nature of the material and the lack of effective learning media pose significant challenges. The use of learning media greatly assists students in understanding the material presented by teachers. In today's technological era, digital learning media and technology integration are essential for students to keep up with advancements. This study aims to assess the feasibility of the Android-based application PERANTARA (Pengetahuan Ragam Nusantara) as a learning media for the IPS material "Indonesiaku Kaya Budaya" for fourth-grade students. The research method employed is Research and Development (R&D) using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The subjects of the study are students from Class VI A at SD Negeri 2 Cipeujeuh Kulon and Class VI B at SD Negeri Sukaraja 1. Results from expert validation indicated scores of 93.75 for content, 87.5 for media, and 90.625 for language, categorizing the application as "Very Feasible." Additionally, trial runs in two schools revealed positive student feedback, with average scores of 84% for small group trials and 87.67% for large group trials, indicating that the PERANTARA application significantly contributes to introducing Indonesia's cultural diversity.